THE LIFE AND WORKS OF THE DAGESTAN SCHOLAR RAHMAN-KULI AL-AHTI (LATE 17TH – EARLY 18TH CENTURY) - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the life and works of Rahman-kuli al-Ahti, a Dagestani scholar and theologian active during the last third of the 17th and first half of the 18th centuries, a figure heretofore underrepresented in scholarly discourse. Previous knowledge of al-Ahti derives primarily from Ali Kayayev’s (1878–1943) biographical compilation, wherein it is noted that al-Ahti translated Muhammad al-Daylami’s Persian medical text, Tukhfat al-mu’minin into Arabic. Analysis of an extant manuscript of this Arabic translation, housed in Ali Kayayev’s library, confirms its status as Rahman-kuli al-Ahti’s autograph, initiated in October 1723. The introduction to this translation, as preserved within Kayayev’s Tarajim ‘ulama’ Daghistan (Biographies of the Scholars of Dagestan), is demonstrably a direct transcription from al-Ahti’s original manuscript. The attribution of this translation to Damadan al-Mukhi, found in some literature, lacks substantiation and is considered improbable. Two manuscripts copied by Rahman-kuli al-Ahti have been identified: one dated 1708, and another completed in 1696 during his studies under Nuruddin Efendi in Kish (present-day Sheki region, Azerbaijan). These manuscripts permit a more precise determination of al-Ahti’s chronology, suggesting his birth occurred between the 1670s and early 1680s. While the precise date of his death remains unknown, it is posited that he died in the first half of the 18th century. Evidence suggests that Rahman-kuli al-Ahti resided substantially outside Dagestan, particularly in Shirvan.